Workshop Pengembangan Bakat terhadap Atlet Basket Muda Kepahiang - Feby Elra Perdima; Deffri Anggara; Dolly Apriansyah; Azuwandri Azuwandri (Universitas Dehasen Bengkulu, 2022)
The purpose of this community service is to increase the talent of Kepahiang Young Basketball Athletes. The training will be divided into 2 stages, where at the initial stage the team will explain the concept of Talent Development for Kepahiang Young Basketball Athletes. This training method is carried out using the tutorial method and FGD so that athletes can improve their basketball skills. This training resulted in a very good response/feedback for the participants, because it was very useful to increase their knowledge about the importance of an exercise program, motivation, teamwork in basketball.